Development and validation of single items for fatigue and recovery in dancers - Jeffries, A. C.; Novak, A. R.; Coutts, A. J.; McCall, A.; McLaren, S. J.; Impellizzeri, F. M. (International Journal of Sports Physiology and Performance, 2023)
Athlete-reported outcome measures (AROMs) are frequently used in practice and research to measure the training response with a dramatic increase in the past 5 years.1 While there are many AROMs and measurement tools available, the most commonly used are the single or "wellness" items, but most have not been properly validated or validated at all.1 Only multiple-item AROMs derived from psychometrics possess adequate levels of evidence for measurement properties, with the exclusion of content validity and measurement error. Therefore, there is a critical need to develop and examine the validity of instruments by adopting appropriate methodology using established reference methods when developing AROMs. The COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) is an established reference set of recommendations that we recently suggested to guide development and validation of measures aimed to assess symptoms and physical signs.